PERANCANGAN SISTEM SELF-ASSESSMENT KESELAMATAN DAN KESEHATAN KERJA (K3) BERBASIS WEBSITE PADA PT PLN (PERSERO) UP3 BANYUWANGI - Sariratul Aisyah; A Hamdani; Cahyo Prabowo (Jurnal Riset Teknik Komputer, 2025)
Occupational Safety and Health (OSH) is an essential aspect in the work environment of PT PLN (Persero) UP3 Banyuwangi. Up to now, OSH implementation has only been carried out manually through attendance checks, visual inspections, and oral reporting, which have not been documented in a database system. This study aims to design a web-based OSH self-assessment system called Safety Vision Control. In this study, self-assessment in understood as the overall process of workers’ self-input before starting work activities, consisting of visual input based on Computer Vision, facial photo capture for expression detection, full-body photo capture for Personal Protective Equipment (PPE) inspection, as well as questionnaire-based input, namely the completion of several questions referred to as the self-check questions feature, which adapts the concept of “5 step to safety” to assess physical condition and work readiness. All of these date are integrated to determine work eligibility. This study employs a qualitative descriptive method using observation, interviews, and literature review techniques. The design outputs include process flow, website interface, and system modeling using UML (use case diagram, activity diagram, sequence diagram, and class diagram). This design is expected to improve the objectivity, efficiency, and documentation of OSH implementation, while also assisting supervisors in making quicker decisions in the field.